The taming of the shrew - Zeffirelli, Franco; Taylor, Elizabeth, 1932-2011; Burton, Richard, 1925-1984 (Columbia TriStar Home Video, 2007)
Ελεύθερη διασκευή και μεταφορά στην οθόνη του ομώνυμου Σαιξπηρικού έργου.